Capitalism reassessed - Pryor, Frederic L. (Cambridge : Cambridge University Press, 2010)
Capitalism Reassessed provides a broad view of different types of advanced capitalist economic systems and is based on an empirical analysis of twenty-one OECD nations. The book looks at why capitalism developed in Western Europe rather than elsewhere. It shows the close influences of the cultural system on the economic system. The analysis compares the economic and social performance of the capitalist economic systems along a variety of economic and social criteria. It also analyzes how capitalism will change in the twenty-first century.
Machine generated contents note: 1. Introduction; 2. What is capitalism?; 3. Origins of capitalism; 4. Varieties of capitalism in industrialized nations; 5. Cultural influences on the economic system; 6. Do some capitalist economic systems perform better than others?; 7. Happiness and capitalist economic systems; 8. How capitalism will change.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Capitalism -- Case studies; Capitalism -- Cross cultural studies